IGFBP5 mediates the therapeutic effect of isoliquiritigenin in myocardial ischemia-reperfusion injury via AKT/GLUT4 regulated insulin resistance - Bai, Jue; Yang, Si-Yuan; Yu, Shao-Mei; Cao, Ying; Ma, Chang-Han; Hu, Xuan-Yi; Chen, Xiong; Song, Ying-Nan; Chen, Hong-Jin (Frontiers in Pharmacology, 2025)
BackgroundMyocardial ischemia/reperfusion injury (MIRI) is a critical problem in cardiovascular medicine, often occurring after coronary revascularization procedures or cardiopulmonary bypass. The characters of MIRI are both energy metabolism disturbances and severe myocardium insulin resistance (IR), which exacerbated myocardial damage and cell death. Isoliquiritigenin (ISL), a flavonoid derived from licorice roots (Glycyrrhiza spp.), has demonstrated protective effects on MIRI. However, the potential cardio-protective effects and mechanism of ISL in MIRI remain unclear.ProposeIn this study, we aimed to investigate ISL’s therapeutic effects on MIRI. Moreover, we elucidate the underlying mechanisms of ISL regulated myocardium insulin resistance in vivo and in vitro.MethodsIn vivo, SD rats underwent left anterior descending coronary artery ligation/reperfusion to induce MIRI. Chest echocardiography was performed to monitor cardiac function post-reperfusion, followed by measurement of myocardial injury and IR markers. In vitro, H9C2 cardiomyocytes subjected to oxygen-glucose deprivation/reperfusion (OGD/R). Markers associated with myocardial injury and IR were assessed. Then, we identified potential therapeutic targets IGFBP5 for MIRI by network pharmacology and molecular docking analysis. Finally, lentivirus were used to silence or over-express IGFBP5 to elucidate the role of IGFBP5 in regulating the therapeutic effects of ISL on IR in MIRI.ResultsIn the present study, In vivo experiments demonstrated that ISL attenuated myocardial infarct size, decreased serum markers of myocardial injury, improved left ventricular systolic function, and enhanced insulin sensitivity. In vitro data revealed that ISL ameliorated glucose uptake and cell survival rate. Furthermore, ISL increased AKT phosphorylation and upregulated membrane-bound GLUT4 (M-GLUT4) protein expression levels. These effects of ISL are mediated by the induction of IGFBP5, as demonstrated using gene-specific shRNA or overexpression for IGFBP5.ConclusionOur results reveal that ISL protects against myocardial damage caused by MIRI through the regulation of IR via the IGFBP5/AKT/GLUT4 pathway.